(untitled) (Meridiano 47 - Journal of Global Studies, 2017)
Resenha do livro DODDS, Felix e STRAUSS, Michael. How to lobby at Intergovernmental meetings. London, Earthscan, 2004, 169 p. ISBN 1-84407-074-3.